A 36-Year-Old Renal Transplant Recipient Female with Leg Ulcer: A Case Report and Brief Review - Ali Monfared; Eftekhari Hojat; Seyed Alireza Mesbah; Abbas Darjani; Seyyede Zeinab Azimi (Case Reports in Infectious Diseases)
Background. Opportunistic infections are common in organ transplant recipients. After 6 months of transplantation, patients have the highest risk of opportunistic infections such as cryptococcosis. Case Presentation. The report presents the case of a 36-year-old female renal transplant recipient, with complaints of few subcutaneous painful and warm nodules and large, warm, erythematous, nontender plaques on the mildly edematous right leg and ankle. Incisional biopsy of the subcutaneous nodule over the leg showed panniculitis with small- to medium-sized vasculitis associated with round yeast forms, and culture of the fragments revealed C. neoformans var. grubii. Conclusions. This article also reviews in brief the treatment of this rare complication. Reviewing the literature showed that since the cryptococcal cutaneous lesions are often nonspecific, the clinical picture solely is not enough to construct a definite diagnosis and there must be a high clinical suspicion.